2022
DOI: 10.1111/ijd.16267
|View full text |Cite
|
Sign up to set email alerts
|

Clinicoepidemiological characteristics of cutaneous tuberculosis in 1458 Indian patients: a retrospective analytical study from a tertiary care center

Abstract: Background Tuberculosis (TB) has been one of the most challenging infectious diseases globally. Cutaneous tuberculosis (CTB) accounts for 0.5-2% of extrapulmonary TB and is often missed owing to its varying morphology and paucibacillary nature. Methods In this retrospective analytical study, we share our 22-year experience to describe the clinicoepidemiological features and treatment response of CTB in 1458 Indian patients. In each patient, detailed history was followed by clinical examination, hematological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…PCR on skin biopsy samples was not performed due to some technical reasons. In pediatric settings, there have been a few reports of LV co‐occurring with tuberculids; none had the presentation, described here 1,6,10,11 . In our patient, skin biopsy from hypopigmented lesions showed changes consistent with tuberculid reminiscent of LS.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…PCR on skin biopsy samples was not performed due to some technical reasons. In pediatric settings, there have been a few reports of LV co‐occurring with tuberculids; none had the presentation, described here 1,6,10,11 . In our patient, skin biopsy from hypopigmented lesions showed changes consistent with tuberculid reminiscent of LS.…”
Section: Discussionmentioning
confidence: 55%
“…Mycobacterial tuberculosis (TB) remains a significant challenge, disproportionately affecting developing countries and underserved communities. Cutaneous TB (CTB) is rare, accounting for a 0.5%–2% of extra‐pulmonary TB 1 . The prevalence of CTB among children in different studies has been reported to range from 19% to 55% 1–5 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations